Nutritional and hormonal strategies to improve fertility in lactating dairy cows - Sauls-Hiesterman, Julie Ann (Kansas State University, 2019)
Four experiments were conducted to assess nutritional and hormonal strategies to improve fertility in lactating dairy cows. In experiment 1, metabolites (-4, -2, +1, +2, +5, and +7 wk) and steroid hormones in ovarian follicular fluid (FF) and blood serum (BS) were examined in Holstein cows (n = 59) individually fed Saccharomyces cerevisiae fermentation product from -4 through +7 wk (calving = wk 0). Neither metabolites nor hormonal concentrations in BS or FF differed between treatments. In experiment 2 a rumen-protected glucose (RPG) product was supplemented at varying doses in the diet of lactating dairy cows with the objective to increase concentrations of glucose and insulin resulting in decreased activity of liver cytochrome P450 2C and P450 3A, thus increasing blood progesterone concentration. Neither pre-feeding nor post-feeding concentrations of glucose differed among treatments. Pre-feeding insulin did not differ among treatments, but a difference in the concentration of insulin (postprandial minus pre-prandial) was detected (P = 0.01). The increase in insulin was greater in control cows relative to the mean of the 3 RPG doses. We conclude that the insulin response to the RPG diets was diminished relative to the control. Supplementation with RPG did not impact concentrations of progesterone. Experiment 3 tested: (1) a shortened version of Ovsynch (SS: GnRH-1 -7 d - PGF₂α - 24 h - PGF₂α - 32 h - GnRH-2 - 16 h - AI) that excluded GnRH-1 to resynchronize ovulation in cows bearing a corpus luteum (CL) after a non-pregnancy diagnosis (NPD); (2) the value of including progesterone-releasing intravaginal insert + Ovsynch (OVS + CIDR) in absence of a CL compared with presence of a CL + OVS; and (3) the accuracy of detecting a functional CL by transrectal ultrasonography. Pregnancy per AI (P/AI) risk tended (P = 0.09)) to be greater for OVS than SS but did not differ from OVS + CIDR at 32 d (30.3% [n = 644], 25.7% [n = 678], and 25.9% [n = 270]), respectively. In SS cows, P/AI was greater (P = 0.01) when cows had a functional CL (progesterone was ≥ 1 ng/mL) vs. a nonfunctional CL at d 0, but did not differ from OVS cows. Short synch is a viable alternative to an entire OVS treatment when CL status is accurately detected. Experiment 4 was performed in 2 herds to determine if administering PGF₂α concurrent with timed artificial insemination in lactating dairy cows would enhance P/AI. Pregnancy per AI at d 32 and 80 did not differ between treatments. Cows treated with PGF₂α in one herd produced more twins than control cows (11.7 vs. 3.2%), whereas no treatment difference was detected in the second herd (5.6 vs. 5.6%), respectively. We conclude that i.m. treatment of lactating dairy cows with 10 mg of PGF₂α concurrent with timed AI did not improve P/AI or embryo survival, but increased twinning in one herd. Further research is warranted to determine nutritional and hormonal strategies to improve fertility.
Keywords: Dairy cow; Nutrition; Fertility